Do espetáculo das arenas de futebol, os efeitos perversos de uma paixão na cidade de São Paulo - Tamura, Fernando Seike (Universidade Federal de São Carlos, 2025)
This work aims to understand how the modernization and commodification of football has contributed to the gentrification of stadiums, impacting the presence and experience of fans. The sport's structural and market transformations have made access more elitist, pushing away popular social groups and weakening the cultural identity of the stands. Through a historical overview, the study reflects on how football, which has always belonged to the people, is becoming a luxury product, and what this means for society and the emotional connection with the sport. In the final considerations, it is concluded that the rampant modernization of the sport alienates its main protagonist, the fan, making it essential to reflect on the direction in which we are taking football.
From the spectacle of soccer arenas, the perverse effects of a passion in the city of São Paulo
Keywords: Arenas de Futebol; Gentrificação; Experiência; Elitização; São Paulo - SP; Football Arenas; Gentrification; Experience; Elitization; São Paulo - SP; CIENCIAS SOCIAIS APLICADAS::TURISMO